ANXIETY AND DEPRESSION AS KEY DETERMINANTS OF CANCER RELATED FATIGUE AMONG PATIENTS RECEIVING CHEMOTHERAPY - Yasin, Yasin M.; Al-Hamad, Areej (European Scientific Journal, ESJ, 2015)
Among non-communicable diseases, cancer is the second leading cause of death worldwide. In Jordan, it is the second leading cause of death. Fatigue is the most reported symptom among cancer patients. The purpose of this study was threefold: (1) to explore the prevalence of fatigue as a side effect of cancer chemotherapy (2) to examine the impact of chemotherapy on fatigue, and (3) to investigate psychological factors (depression and anxiety) that correlate with fatigue. A one group before and after quasi-experimental design was used to conduct this study. The Integrated Fatigue Model (IFM) was used to guide the study. A Convenience sampling technique was used to recriut78 participants diagnosed with cancer and treated with chemotherapy as the primary treatment. The sample was collected from two well-known Jordanian hospitals. Fatigue was measured using Piper Fatigue Scale (PFS) and the psychological variables (depression and anxiety) were measured using Hospital Anxiety and Depression Scale (HADS). Findings revealed an increase incidence of fatigue after a chemotherapy course. Also revealed was a statistically significant difference between pre and post chemotherapy fatigue mean total scores as well as behavioral, affective, sensory and cognitive dimensions. It was found that depression and anxiety have a positive relationship with fatigue. Depression explained 46% of fatigue score variance. Furthermore, anxiety explains 3.6% of the variance in fatigue scores. It could be concluded that fatigue is a prevalent symptom among cancer patients receiving chemotherapy. Depression and anxiety were identified as possible predictors of fatigue among cancer patients receiving chemotherapy.